2013
DOI: 10.1017/s003329171300069x
|View full text |Cite
|
Sign up to set email alerts
|

Peer problems are associated with elevated serum leptin levels in children

Abstract: Children with peer problems have higher stress and eat more, acquire a higher body fat mass and thus, through increased leptin resistance, exhibit higher leptin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…To our knowledge, this is the first prospective epidemiological study investigated associations between fetal adipokine levels and child behavioral problems. Child behavioral problems in association with obesity, overweight and high BMI have been reported through cross-sectional studies [ 24 , 25 , 26 ]. Similarly, several previous studies investigated child behavioral problems and cognitive and motor development in association with leptin levels in cross-sectional studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first prospective epidemiological study investigated associations between fetal adipokine levels and child behavioral problems. Child behavioral problems in association with obesity, overweight and high BMI have been reported through cross-sectional studies [ 24 , 25 , 26 ]. Similarly, several previous studies investigated child behavioral problems and cognitive and motor development in association with leptin levels in cross-sectional studies [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As leptin is a major regulator of bone mass [10], a leptin deficiency may alter the BMD [34]. Leptin is also increased by emotional stress, which is also one of the many environmental factors potentially leading to obesity [35,36].…”
Section: Adiposity-bone Metabolism Cross-talkmentioning
confidence: 99%
“…In our study, significances were only found in girls: leptin levels were higher with higher daily cortisol output. Indeed, sex‐differences have previously been mentioned in the associations with significant results in women only. Moreover, sex differences have been revealed in leptin levels, due to testosterone‐induced leptin downregulation but also in prepubertal child populations .…”
Section: Discussionmentioning
confidence: 96%
“…In an increasing amount of studies, psychosocial stress has been associated with higher leptin levels in adults and in children only for peer/emotional problems . Nevertheless, depression has also been associated with lower leptin levels and some studies found no significant associations with adult depression or child trauma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation